Maternal oxygen exposure may not change umbilical cord venous partial pressure of oxygen: non-random, paired venous and arterial samples from a randomised controlled trial - Yunhai Chuai; Wen Jiang; Xiaobin Xu; Aiming Wang; Yuanqing Yao; Lei Chen (BMC, 2020)
Abstract Background Despite the widespread use of oxygen (O2) in intrauterine resuscitation, the obstetric scientists' understanding of O2 therapy is full of contradictions. We tested the hypothesis that higher maternal arterial partial pressure of oxygen (PO2) is associated with higher umbilical cord venous PO2 (UvPO2). Methods This is a planned secondary analysis of a randomised controlled trial (RCT), 443 normal women were 1:1 randomly allocated to receive 2 L/min O2 or room air from the onset of second stage to delivery. We reported that maternal 2 L/min O2 exposure cannot affect the umbilical cord arterial pH or the fetal heart rate (FHR) pattern. In 217 non-random samples, we found 2 L/min O2 exposure increased the maternal arterial PO2 to the median 150 mmHg (hemoglobin would be saturated). The primary outcome for this analysis was UvPO2 in these non-random samples. Results There were no significant differences between the O2 group (N = 107) and the control group (N = 110) in the UvPO2 (median 30.2, interquartile 25.4-35.2 versus median 28.3, interquartile 23.4-35.3, mmHg, P = 0.379). There were also no significant differences between room air and different percentiles of O2 exposure duration (< 25th, ≧ 25th < 50th, ≧ 50th < 75th, ≧ 75th percentile) in the UvPO2. Conclusions Maternal O2 exposure at super-physiological levels (median arterial blood PO2 150 mmHg) in normal labor may not change the UvPO2. Clinical trial registration ClinicalTrials.gov NCT02221440 , first posted in 20 August 2014.